Semaphorin 4C Plexin-B2 signaling in peripheral sensory neurons is pronociceptive in a model of inflammatory pain - Paldy, Eszter; Simonetti, Manuela; Bali, Kiran Kumar; Vicuña Zauschkevich, Lucas; Kuner, Rohini (Nature Communications, 2017)
Semaphorins and their receptors are involved in neurodevelopment, but their functions in the adult nervous system are not fully understood. This study finds that semaphorin 4C and its receptor Plexin B are expressed in sensory neurons and are pronociceptive in a mouse model of inflammatory pain.